Acalabrutinib monotherapy in patients with Waldenström macroglobulinemia: a single-arm, multicentre, phase 2 study. Issue 2 (February 2020) - Owen, Roger G; McCarthy, Helen; Rule, Simon; D'Sa, Shirley; Thomas, Sheeba K; Tournilhac, Olivier; Forconi, Francesco; Kersten, Marie José; Zinzani, Pier Luigi; Iyengar, Sunil; Kothari, Jaimal; Minnema, Monique C; et al.
Summary: Background: Chemoimmunotherapy is typically the standard of care for patients with Waldenström macroglobulinemia; however, infectious and hematologic toxic effects are problematic. Acalabrutinib is a selective, potent Bruton tyrosine-kinase inhibitor. The aim of this trial was to evaluate the activity and safety of acalabrutinib in patients with Waldenström macroglobulinemia. Methods: This single-arm, multicentre, phase 2 trial was done in 19 European academic centres in France, Italy, Greece, the Netherlands, and the UK, and eight academic centres in the USA. Eligible patients were 18 years or older and had treatment naive (declined or not eligible for chemoimmunotherapy) or relapsed or refractory (at least one previous therapy) Waldenström macroglobulinemia that required treatment, an Eastern Cooperative Oncology Group performance status of 2 or less, and received no previous Bruton tyrosine-kinase inhibitor therapy. Patients received 100 mg oral acalabrutinib twice per day in 28-day cycles until disease progression or unacceptable toxicity. The primary endpoint was investigator-assessed overall response (at least a minor response) according to the 6th International Workshop for Waldenström Macroglobulinemia (IWWM) and the modified 3rd IWWM workshop criteria. The primary outcome and safety were assessed in all patients who received at least one dose of treatment. This study is registered with ClinicalTrials.gov, number NCT02180724, and is ongoing, but no longer enrolling. Findings: Between Sept 8, 2014, and Dec 24, 2015, 122 patients were assessed for eligibility, of which 106 (87%) patients were given acalabrutinib (14 were treatment naive and 92 had relapsed or refractory disease). With a median follow-up of 27·4 months (IQR 26·0–29·7), 13 (93% [95% CI 66–100]) of 14 treatment naive patients achieved an overall response and 86 (93% [86–98]) of 92 relapsed or refractory patients per both the modified 3rd and 6th IWWM criteria. Seven (50%) of 14 treatment naive patients and 23 (25%) of 92 relapsed or refractory patients discontinued treatment on study. Grade 3–4 adverse events occurring in more than 5% of patients were neutropenia (17 [16%] of 106 patients) and pneumonia (7 [7%]). Grade 3–4 atrial fibrillation occurred in one (1%) patient and grade 3–4 bleeding occurred in three (3%) patients. The most common serious adverse events were lower respiratory tract infection (n=7 [7%]), pneumonia (n=7 [7%]), pyrexia (n=4 [4%]), cellulitis (n=3 [3%]), fall (n=3 [3%]), and sepsis (n=3 [3%]). Pneumonia (n=5 [5%]) and lower respiratory tract infection (n=4 [4%]) were considered treatment related. One treatment-related death was reported (intracranial hematoma). Interpretation: This study provides evidence that acalabrutinib is active as single-agent therapy with a manageable safety profile in patients with treatment-naive, or relapse or refractory Waldenström macroglobulinemia. Further studies are needed to establish its efficacy against current standard treatments and to investigate whether outcomes can be improved with combination therapies. Funding: Acerta Pharma.